Microsecond time‐resolved X‐ray diffraction for the investigation of fatigue behavior during ultrasonic fatigue loading. (20th August 2019) - Ors, T.; Ranc, N.; Pelerin, M.; Michel, V.; Favier, V.; Castelnau, O.; Mocuta, C.; Thiaudière, D.
Abstract : The time‐resolved X‐ray diffraction technique is proposed to characterize the fatigue behavior of metallic materials during ultrasonic cyclic loading. Abstract : A new method based on time‐resolved X‐ray diffraction is proposed in order to measure the elastic strain and stress during ultrasonic fatigue loading experiments. Pure Cu was chosen as an example material for the experiments using a 20 kHz ultrasonic fatigue machine mounted on the six‐circle diffractometer available at the DiffAbs beamline on the SOLEIL synchrotron facility in France. A two‐dimensional hybrid pixel X‐ray detector (XPAD3.2) was triggered by the strain gage signal in a synchronous data acquisition scheme (pump–probe‐like). The method enables studying loading cycles with a period of 50 µs, achieving a temporal resolution of 1 µs. This allows a precise reconstruction of the diffraction patterns during the loading cycles. From the diffraction patterns, the position of the peaks, their shifts and their respective broadening can be deduced. The diffraction peak shift allows the elastic lattice strain to be estimated with a resolution of ∼10 −5 . Stress is calculated by the self‐consistent scale‐transition model through which the elastic response of the material is estimated. The amplitudes of the cyclic stresses range from 40 to 120 MPa and vary linearly with respect to the displacement applied by the ultrasonic machine. Moreover, the experimental results highlight an increase of the diffraction peak broadening with the number of applied cycles.